The miRNA pathway intrinsically controls self-renewal of Drosophila germline stem cells. - Park, J.K.; Liu, X.; Strauss, T.J.; McKearin, D.M.; Liu, Q. (Current Biology, 2007)
Stem cells uniquely self-renew and maintain tissue homoeostasis by differentiating into different cell types to replace aged or damaged cells [1]. During oogenesis of Drosophila melanogaster, self-renewal of germline stem cells (GSCs) requires both intrinsic signaling mechanisms and extrinsic signals from neighboring niche cells [2]. Emerging evidence suggests that microRNA (miRNA)-mediated translational regulation may also control Drosophila GSC self-renewal [3, 4]. It is unclear, however, whether the miRNA pathway functions within stem cells or niche cells to maintain GSCs. In Drosophila, Dicer-1 (Dcr-1) and the double-stranded RNA binding protein Loquacious (Loqs) catalyze miRNA biogenesis [3-5]. Here, we generate loqs knockout (loqs(KO)) flies by ends-out homologous recombination and show that loqs is essential for embryonic viability and ovarian GSC maintenance. Both developmental and miRNA processing defects are rescued by transgenic expression of Loqs-PB, but not Loqs-PA. Furthermore, mosaic germline analysis indicates that Loqs is required intrinsically for GSC maintenance. Consistently, GSCs are restored in loqs mutant ovaries by germline expression, but not somatic expression, of Loqs-PB. Together, these results demonstrate that Loqs-PB, but not Loqs-PA, is necessary and sufficient for Drosophila development and the miRNA pathway. Our study strongly suggests that miRNAs play an intrinsic, but not extrinsic, role in Drosophila female GSC self-renewal.